Effects of High-Intensity Resistance Training on Osteopenia and Sarcopenia Parameters in Older Men with Osteosarcopenia—One-Year Results of the Randomized Controlled Franconian Osteopenia and Sarcopenia Trial (FrOST) - Kemmler, Wolfgang; Kohl, Matthias; Froehlich, Michael; Jakob, Franz; Engelke, Klaus; von Stengel, Simon; Schöne, Daniel (Journal of Bone and Mineral Research, 2020)
Dynamic resistance exercise (DRT) might be the most promising agent for fighting sarcopenia in older people. However, the positive effect of DRT on osteopenia/osteoporosis in men has still to be confirmed. To evaluate the effect of low-volume/high-intensity (HIT)-DRT on bone mineral density (BMD) and skeletal muscle mass index (SMI) in men with osteosarcopenia, we initiated the Franconian Osteopenia and Sarcopenia Trial (FrOST). Forty-three sedentary community-dwelling older men (aged 73 to 91 years) with osteopenia/osteoporosis and SMI-based sarcopenia were randomly assigned to a HIT-RT exercise group (EG; n = 21) or a control group (CG; n = 22). HIT-RT provided a progressive, periodized single-set DRT on machines with high intensity, effort, and velocity twice a week, while CG maintained their lifestyle. Both groups were adequately supplemented with whey protein, vitamin D, and calcium. Primary study endpoint was integral lumbar spine (LS) BMD as determined by quantitative computed tomography. Core secondary study endpoint was SMI as determined by dual-energy X-ray absorptiometry. Additional study endpoints were BMD at the total hip and maximum isokinetic hip−/leg-extensor strength (leg press). After 12 months of exercise, LS-BMD was maintained in the EG and decreased significantly in the CG, resulting in significant between-group differences (p < 0.001; standardized mean difference [SMD] = 0.90). In parallel, SMI increased significantly in the EG and decreased significantly in the CG (p < 0.001; SMD = 1.95). Total hip BMD changes did not differ significantly between the groups (p = 0.064; SMD = 0.65), whereas changes in maximum hip−/leg-extensor strength were much more prominent (p < 0.001; SMD = 1.92) in the EG. Considering dropout (n = 2), attendance rate (95%), and unintended side effects/injuries (n = 0), we believe our HIT-RT protocol to be feasible, attractive, and safe. In summary, we conclude that our combined low-threshold HIT-RT/protein/vitamin D/calcium intervention was feasible, safe, and effective for tackling sarcopenia and osteopenia/osteoporosis in older men with osteosarcopenia. © 2020 American Society for Bone and Mineral Research. © 2020 American Society for Bone and Mineral Research.
CRIS-Team Scopus Importer:2020-05-12
Keywords: AGING; BONE QCT; EXERCISE; OSTEOPOROSIS; SARCOPENIA